2022
DOI: 10.1186/s12888-022-03887-2
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome study of a salutogenic psychoeducational recovery oriented intervention (Inte.G.R.O.) in severe mental illness patients

Abstract: Aim Inte.G.R.O. is a standardized Salutogenic-Psychoeducational intervention designed to help people with severe mental illness manage their life-stress and achieve personal recovery goals through the improvement of social functioning. The aim of this study is to evaluate the long-term outcome of this approach, characterized by health promotion rather than correction of dysfunctional strategies. Methods 41 people underwent an observational study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…This intervention, conducted in a group setting, was delivered online using telemedicine/telerehabilitation technology tools (internet connection, Zoom app). The e-health psychoeducation intervention adopted the same logical framework in comparison to existing, effective traditional psychoeducational models [ 40 , 56 , 57 ]. The overall objective was to provide information about the clinical condition and symptoms, while identifying effective coping strategies to manage mental health and reduce the clinical impact of the pathology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This intervention, conducted in a group setting, was delivered online using telemedicine/telerehabilitation technology tools (internet connection, Zoom app). The e-health psychoeducation intervention adopted the same logical framework in comparison to existing, effective traditional psychoeducational models [ 40 , 56 , 57 ]. The overall objective was to provide information about the clinical condition and symptoms, while identifying effective coping strategies to manage mental health and reduce the clinical impact of the pathology.…”
Section: Methodsmentioning
confidence: 99%
“…All sessions included an informative section (15 min); the identification of personal strategies (20 min); learning through commonly used techniques, such as shaping, scaffolding, or role-playing (45 min); and finally, a section with home assignments identified as recovery goals (10 min). In this context, a salutogenic, personal, recovery-oriented model was promoted [ 56 , 59 , 60 ], emphasizing strategies to manage the effects of the pandemic in daily life, and aligning with participants’ personal goals and the specific needs of the target population.…”
Section: Methodsmentioning
confidence: 99%
“…A review examining the effects of psychological interventions on alexithymia concluded that it is partly modifiable with these therapeutic interventions, offering suggestions for future research [ 94 ]. Similarly, salutogenic-based approaches offer promising results, strengthening sense of coherence and effectuating positive outcomes in key variables for personal recovery in people with schizophrenia [ 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%